How external auditor quality moderates the relation between internal audit committee effectiveness and accounting conservatism. (18th August 2021) - Ur-Rehman, Saif; Khan, Faisal; Hemdan, Dalia Ali Mostafa; Khan, Hashim
This study examines the effect of audit committee on two measures of accounting conservatism. In addition, this study also investigates the interaction effect of exogenous variable (i.e., external auditor quality) on relationship between audit committee effectiveness and two measures of accounting conservatism. A total of 38 sample firms are selected from the Nasdaq Dubai for the period from 2013 to 2017. In addition, some information relating to audit committee and auditor quality are collected from firms' annual reports. For data analysis, panel data methodology is employed and multiple regression analysis technique is used to test the developed hypotheses of this study. Results show that interaction effect of external auditor quality found to be significant with one-year-lagged effect on both measures of conservatism. The findings of this study contribute to the signalling theory, agency theory, reputation theory and accounting conservatism literature with lagged effect in emerging economies settings.